Phytochemical study of Ruellia tuberosa chloroform extract: Antioxidant and anticholinesterase activities - Supawana Khachitpongpanit (2018)
Ruellia tuberosa is a tropical plant in Acanthaceae family that has been used as folk medicine and widely distributed in South East Asia. This study was conducted to determine phytochemical content, antioxidant and anticholinesterase activity of chloroform extracts including leaves, stem and root of R. tuberosa, collected from Chiang Mai, Thailand. Total phenolic, flavonoid, tannin and alkaloid contents were determined for all of the extracts.1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay, nitric oxide scavenging assay, reducing power and ferric reducing antioxidant power (FRAP) were used as an antioxidant models. Anticholinesterase activity was determined using Ellman's assay. The results showed that R. tuberosa leaves extract displayed the highest phenolic, flavonoid, tannin and alkaloid contents with 0.16±0.01 μg gallic acid equivalent/g extract, 1.55±0.13 μg quercetin equivalent/g extract, 0.20±0.04 μg tannic acid equivalent/g extract and 1.62±0.01 μg strychnine equivalent/g extract, respectively. Leave extract also had the highest potential to scavenge DPPH and nitric oxide radical while stem and root extract could inhibit both acetylcholinesterase and butyrylcholinesterase at concentration 200 μg/ml with low free radicals scavenging.